Evaluation of the Prognostic Utility of Computed Tomography New Severity Score in COVID-19 Pneumonia Patients - Ozlem Gungor; Cansu Ozturk; Zehra Nur Sesen; Aslihan Burcu Yikilan; Selma Uysal Ramadan; Seref Kerem Corbacioglu (Haseki Tıp Bülteni)

(untitled)
Aim:To investigate the relationship between infection markers (lymphocyte, C-reactive protein, and D-dimer) at the time of diagnosis, and the new scoring system created according to the amount and pattern of pneumonic involvement in recent computed tomography (CT) of patients with Coronavirus disease-2019 (COVID-19) pneumoniaMethods:We investigated retrospectively patients diagnosed with COVID-19 with positive reverse transcriptase-polymerase chain reaction on throat swabs between March 17 and May 1, 2020. Eighty-nine cases with COVID-19 pneumonia were divided into two groups according to the level of poor prognostic criteria (blood lymphocyte count <800/μL or C-reactive protein >10x upper limit of normal value or D-dimer >1000 ng/mL). The severity of pulmonary parenchymal findings was scored using two separate scoring systems previously as well as a third separate scoring system, namely the “modified CT severity scoring”. The cut-off point for severe infection was investigated by comparing the scores of the groups with and without severe infection.Results:All three scoring systems were significantly higher in the group with severe infection compared to those without severe infections. A modified CT score above 3.4 accompanies at least one of the poor prognosis findings (sensitivity 77.6%, specificity 61%).Conclusion:In patients with COVID-19 pneumonia, the presence of at least one of the infection markers that are poor prognosis markers at the time of diagnosis indicate that the modified CT severity score of pneumonia will be above 3.4.